Desenvolvimento de uma metodologia para a avaliação da confiabilidade dos ajustes de relés diferenciais de transformadores baseada no Método de Monte Carlo - João Ricardo da Mata Soares de Souza (2012)
Nowadays, there are several functions avaliable in digital protective relays related to eletromagnetic transients, whose detailed analysis may be done only at time domain. Transformer differential protective relays are an example of this. Schemes developed to detect inrush currents, overexcitation and current transformers saturation are types of functions related to electromagnetic transients avaliable at differential relays.Despite of this, the setting of this protective relays is often based only on frequency domain studies, such as fault and load flow analysis. Functions related to electromagnetic transients are set based on manufacturer recommendations, on generic studies made in the past or on experience. This procedure does not take into account particularities from each situation, which may compromise the whole protection system performance. The aim of this dissertation is to present a time domain analysis methodology to support transformer differential protective relays setting. This methodology use concepts related to the Reliability Theory and to Monte Carlo methods and computational tools such as Scilab and ATP (Alternative Transient Program).